NILAI-NILAI SOSIAL DALAM KUMPULAN CERPEN BH KARYA EMHA AINUN NADJIB - Norminawati, Siti; Martono, Martono; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe researcher aims to gain an overview of social values in the BH a collection of short stories by Emha Ainun Nadjib. Benefits of research that can be obtained from this research that is, theoretical benefits and practical benefits. Theories used in this research is, the theory of social value and short stories. Researchers use descriptive and qualitative methods.The approach used, the approach of the sociology of literary works. The data sources in this study relate to the social values associated with divinity, the social values associated with the individual, and the social values associated with the society depicted in words, phrases, and sentences in the of BH a collection of short stories by Emha Ainun Nadjib. Based on the results of research data on the of BH a collection of short stories by Emha Ainun Nadjib, it can be concluded that there are social values associated with divinity, the form of social value is to pray to God, believe in the Providence of God, and fear God. Social values associated with the individual, the form of social value is the value of responsibility, the value of honesty, the value of dedication, the value of tolerance, the value of consciousness, and the value of strong desire. Social value associated with society, the form of social value is the value of caring, the value of help-help, and the value of affection.Â Keywords: social values, a collection of short stories, BH